2021
DOI: 10.1002/app.51897
|View full text |Cite
|
Sign up to set email alerts
|

High thermal conductivity graphene oxide/carbon nanotubes/butyl rubber composites prepared by a dry ice expansion pre‐dispersion flocculation method

Abstract: Butyl rubber (IIR) is widely used in tire inner liners and tubes, vulcanization bladders, and shock absorption materials due to its extremely low air permeability, excellent aging resistance, and good energy absorption. However, its low thermal conductivity affects its performance and the service life of the product, while it also limits its application. Therefore, the preparation of butyl rubber composites with high thermal conductivity is of great significance and practical value. This paper proposes the use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 41 publications
(33 reference statements)
0
4
0
Order By: Relevance
“…The latex mixing [ 100 , 101 , 114 ] and mechanical mixing [ 115 , 116 , 117 ] methods have also been used for preparing GE/CNT/rubber composites. Li et al [ 100 ] combined GE and CNTs hybrid fillers to reinforce NR, wherein GE/CNT/NR composites were prepared using in situ reduction with NR latex.…”
Section: Rubber Composites With Different Graphene Hybrid Fillersmentioning
confidence: 99%
“…The latex mixing [ 100 , 101 , 114 ] and mechanical mixing [ 115 , 116 , 117 ] methods have also been used for preparing GE/CNT/rubber composites. Li et al [ 100 ] combined GE and CNTs hybrid fillers to reinforce NR, wherein GE/CNT/NR composites were prepared using in situ reduction with NR latex.…”
Section: Rubber Composites With Different Graphene Hybrid Fillersmentioning
confidence: 99%
“…This method is more eco-friendly compared with solution blending. However, the large amount of deionized water used to disperse CNT dilutes the latex, which makes the CNT tend to settle in the diluted latex and leads to a secondary agglomeration [ 16 ]. Traditional mechanical blending disperses CNT in the matrix by strong shear mixing using an internal mixer, two-roll mill, ball mill, etc.…”
Section: Introductionmentioning
confidence: 99%
“…However, the aggregation of polar fillers is relatively serious during dry mixing, with rapid heat generation, easy scorching, high energy consumption, and serious dust pollution 5 . Wet mixing is the process in which the filler is made into water dispersion, fully mixed with latex in the liquid state, then flocculated, dewatered, and dried to finally prepare the rubber masterbatch 6–8 . Wet mixing not only significantly improves the dispersion of reinforcing fillers, and prepares high‐performance rubber compounds with high filler content, but also reduces energy consumption and adapts to the development of green and energy conservation 9,10 .…”
Section: Introductionmentioning
confidence: 99%
“…5 Wet mixing is the process in which the filler is made into water dispersion, fully mixed with latex in the liquid state, then flocculated, dewatered, and dried to finally prepare the rubber masterbatch. [6][7][8] Wet mixing not only significantly improves the dispersion of reinforcing fillers, and prepares high-performance rubber compounds with high filler content, but also reduces energy consumption and adapts to the development of green and energy conservation. 9,10 Xuan et al 11 compared the mixing power curves of rubber compounds by dry mixing and wet mixing, and the results showed that compared with dry mixing, wet mixing reduced the energy consumption by 30%, improved the dispersion of fillers and the mechanical properties of composites.…”
mentioning
confidence: 99%